DOES MORAL HAZARD OCCOUR IN THE IMPLEMENTATION OF SOCIAL HEALTH INSURANCE? EVIDENCE FROM PUBLIC HOSPITALS IN A RURAL PROVINCE OF INDONESIA - Rizanda Machmud; Syafrawati Syafrawati; Prof. Syed Mohamed Aljunid; Rima Semiarty (Asia Pacific Fraud Journal, 2020)
Indonesia is now encountering moral hazard problems in the implementation of social health insurance. BPJS, as the administrator of Indonesia’s National Health Insurance, reported that there was an increase in deficit in the 4 years of the implementation of National Health Insurance from US$ 228 million in 2014 to US$ 470 million in 2016. Despite efforts conducted to overcome the problem, no evidence-based predictor that might be significantly associated with moral hazard in a rural province hospital in Indonesia. The purpose of this research is to identify the incidence of moral hazard in the implementation of National Health Insurance in Indonesia. Data consisting of 180 medical records obtained from three public hospitals in rural province of Indonesia were selected as samples in this study. These medical records were reviewed by Independent Senior Coder (ISC) who had more than 5 years experiences as a coder. The indicators of moral hazard in this study were upcoding, readmission, and possible unnecessary admission. Logistic regression was used to explore determinant of moral hazard from patient, coder, and physician side. The results show that rate of moral hazard cases for upcoding is 10%, readmission is 2.8%, and possible unnecessary admission is 18.9%. It can be seen from multivariate analysis that discharge status, severity level and LOS have a significant relationship with moral hazard. Illness severity level, Discharge against Medical Advice, and higher Length of Stay are risk factors for moral hazard incidence.